Development of Quadric Surfaces Learning Tool for Engineering Students using MATLAB GUI - Suhaila Abd Halim; Zuraida Alwadood; Norlenda Mohd Noor; Hanifah Sulaiman (Journal of Advanced Research in Computing and Applications, 2023)
Mathematics is the most challenging subject to learn even in higher learning education. The problem encountered in learning mathematics could lead to the lack of interest in understanding the concepts in mathematics. In the development of communication technology, it is believed that hybrid learning environment can be an initiative in improving learning system. Face to face classroom delivery with utilization of application tool and system become useful in this type of environment. This paper aims to the development of learning tool using MATLAB GUI for multivariable functions of quadric surfaces. This paper focus on this topic as student feels difficulty in understanding the concepts in that topic. It is believed that this tool able to help student to visualize the concepts effectively for more understanding.